Healthy adult gut microbiota sustains its own vitamin B12 requirement in an in vitro batch fermentation model - Kundra, Palni; Geirnaert, Annelies; Pugin, Benoit; Morales Martinez, Paola; Lacroix, Christophe; Greppi, Anna (Frontiers in Nutrition, 2022)
Vitamin B12 (cobalamin) is present in the human lower gastrointestinal tract either coming from the unabsorbed dietary fraction or from in situ production of the gut microbiota. However, it is unclear whether the gut microbial communities need exogenous B12 for growth and metabolism, or whether over-supplementing or depleting B12 from the diet could affect gut community composition and metabolite production. Here, we investigated in vitro B12 production of human faecal microbiota and the effects of over supplementation or depletion of B12 (as cyanocobalamin) on composition and activity. Eight faecal communities from healthy human adults distributed over three enterotypes, dominated by Firmicutes (n = 5), Bacteroides (n = 1) or Prevotella (n = 2) were used to perform batch fermentations in Macfarlane medium supplemented with low B12 medium (Control, 5 ng/ml, within the tested faecal range), no B12 addition (NB12), and high B12 addition (ExtraB12, 2500 ng/ml). The microbiota community composition (qPCR, 16S rRNA metabarcoding), metabolic activity (HPLC-RI), and B12 levels (UHPLC-DAD) were measured after 24 h incubation at 37° C under strict anaerobic conditions. All faecal microbial communities produced B12 in the NB12 condition after 24 h, in the range from 152 ± 4 to 564 ± 25 ng/ml. None of the B12 treatments, supplementation, or depletion, had an impact on total bacterial growth, community richness, diversity and total metabolite production, compared to the low B12 control. However, a significant increase of propionate was measured in ExtraB12 compared to NB12. Most taxonomic and metabolite changes compared to control incubations were donor-dependent, implying donor-microbiota-specific changes upon B12 treatments. Our in vitro data suggest that healthy human adult gut microbial communities have the capacity to produce B12 at levels fulfilling their own requirements, independently of the initial B12 content tested in the donor’s faeces. Further, supplementation of exogenous dietary B12 may have limited impact on the healthy human gut microbial community composition and function.